The fast-rotating, low-gravity subdwarf B star EC22081-1916: Remnant of a common envelope merger event - Geier, Stephan; Classen, Lew; Heber, Ulrich (Astrophysical Journal Letters, 2011)
Hot subdwarf B stars (sdBs) are evolved core helium-burning stars with very thin hydrogen envelopes. In order to form an sdB, the progenitor has to lose almost all of its hydrogen envelope right at the tip of the red-giant branch. In binary systems, mass transfer to the companion provides the extraordinary mass loss required for their formation. However, apparently single sdBs exist as well and their formation has been unclear for decades. The merger of helium white dwarfs (He-WDs) leading to an ignition of core helium burning or the merger of a helium core and a low-mass star during the common envelope phase have been proposed as processes leading to sdB formation. Here we report the discovery of EC22081-1916 as a fast-rotating, single sdB star of low gravity. Its atmospheric parameters indicate that the hydrogen envelope must be unusually thick, which is at variance with the He-WD merger scenario, but consistent with a common envelope merger of a low-mass, possibly substellar object with a red-giant core. © 2011. The American Astronomical Society. All rights reserved.
CRIS-Team Scopus Importer:2020-12-21
Keywords: branch; stars: horizontal; stars: individual (EC 22081-1916)